Problematika Hukum Pemanfaatan Lagu dan/atau Musik sebagai Objek Jaminan Pembiayaan Perbankan di Era Ekonomi Kreatif - Irgi Alfian (Jurnal Hukum Lex Generalis, 2025)
This study aims to analyze the benefits of songs and/or music that provide economic benefits to creators and/or copyright holders to be used as an object of fiduciary guarantee in banking institutions in supporting the creative economy sector that can support the development of the country's economy. The results of this study show that the legal basis of songs and/or music used as fiduciary guarantees in bank institutions has been regulated in the applicable regulations, the use of songs and/or music as fiduciary guarantees has not been optimally implemented and is not in line with the applicable provisions so that creative economy actors do not feel the benefits of songs and/or music as collateral objects. As a form of implementation of the provisions, the role of the government should be to provide socialization in an integrated manner with related institutions in improving the creative economy sector and realizing a good creative economy ecosystem.